Preliminary - Gómez Botero, Maryory Astrid (Revista Facultad de Ingeniería Universidad de Antioquia, 2015)
Since March 12, this year, the Revista Facultad de Ingeniería has been assigned an online ISSN (e-ISSN: 2422-2844), which can be seen at the top of this issue’s cover. Considering that digital publications are in state of tremendous growth, we hopefully expect our online journal to reach a broader spectrum of readership by having this identification, since our journal was only recognized by the printed serial number.